A QTL atlas for grain yield and its component traits in maize (Zea mays). (6th March 2020) - Zhou, Zhipeng; Li, Guoliang; Tan, Siyu; Li, Dongdong; Weiß, Thea Mi; Wang, Xiangfeng; Chen, Shaojiang; Würschum, Tobias; Liu, Wenxin
Abstract: Grain yield and its component traits are essential targets in maize breeding. These traits are genetically complex and controlled by a large number of quantitative trait loci (QTL). The aim of this study was to compile reported QTL and major genes for grain yield and its component traits in a QTL atlas, as a valuable resource for the maize community. To this end, 1, 177 QTL related to maize yield were collected from 56 studies published between 1992 and 2018. These QTL were projected to genetic map "IBM2 2008 Neighbors", which led to the identification of 135 meta‐QTL. Some genomic regions appear to be hotspots for yield‐related meta‐QTL, often affecting more than one of the investigated traits. Moreover, we catalogued 20 major maize loci associated with yield and identified 65 maize homologs of 21 rice yield‐related genes. Interestingly, we found that a significant proportion of them are located in meta‐QTL regions. Collectively, this study provides a reference for QTL fine‐mapping and gene cloning, as well as for molecular marker‐assisted breeding of yield‐related traits in maize.